Brief preoperative mind–body therapies for total joint arthroplasty patients: a randomized controlled trial. Issue 6 (June 2021) - Hanley, Adam W.; Gililland, Jeremy; Erickson, Jill; Pelt, Christopher; Peters, Christopher; Rojas, Jamie; Garland, Eric L.
Abstract : Abstract: Although knee and hip replacements are intended to relieve pain and improve function, up to 44% of knee replacement patients and 27% of hip replacement patients report persistent postoperative joint pain. Improving surgical pain management is essential. We conducted a single-site, 3-arm, parallel-group randomized clinical trial conducted at an orthopedic clinic, among patients undergoing total joint arthroplasty (TJA) of the hip or knee. Mindfulness meditation (MM), hypnotic suggestion (HS), and cognitive-behavioral pain psychoeducation (cognitive-behavioral pain psychoeducation) were each delivered in a single, 15-minute group session as part of a 2-hour, preoperative education program. Preoperative outcomes—pain intensity, pain unpleasantness, pain medication desire, and anxiety—were measured with numeric rating scales. Postoperative physical functioning at 6-week follow-up was assessed with the Patient-Reported Outcomes Measurement Information System Physical Function computer adaptive test. Total joint arthroplasty patients were randomized to preoperative MM, HS, or cognitive-behavioral pain psychoeducation (n = 285). Mindfulness meditation and HS led to significantly less preoperative pain intensity, pain unpleasantness, and anxiety. Mindfulness meditation also decreased preoperative pain medication desire relative to cognitive-behavioral pain psychoeducation and increased postoperative physical functioning at 6-week follow-up relative to HS and cognitive-behavioral pain psychoeducation. Moderation analysis revealed the surgery type did not differentially impact the 3 interventions. Thus, a single session of a simple, scripted MM intervention may be able to immediately decrease TJA patients' preoperative clinical symptomology and improve postoperative physical function. As such, embedding brief MM interventions in surgical care pathways has the potential to improve surgical outcomes for the millions of patients receiving TJA each year. Abstract : Supplemental Digital Content is Available in the Text. A single session of a simple, scripted mindfulness-based intervention delivered before surgery decreased knee and hip replacement patients' preoperative pain, anxiety, and medication desire as well as accelerated their postoperative recovery of physical function.